High Reading Literacy, Low Character? Exploratory-Descriptive Study of Literacy Learning Based on Cognitive Level L1-L3 in Superior High School Students - Siti Agustini; Ribut Wahyuni Eriyanti; Masduki; Lilis Ernawati (Women, Education, and Social Welfare, 2026)
This study is an exploratory-descriptive study to determine the factors that cause the misalignment between the achievement of reading literacy ability and the character achievement of students from three high schools in East Java. Using qualitative descriptive methods, data was collected through open-ended interviews and literature studies as well as school documents. Researchers choose key informants and specialists because they are considered to have the initial information needed. Data analysis techniques using the Miles-Huberman technique include: data condensation; data display; and conclusion drawing/ verivication. Hasil kategori data: (1) reading literacy achievement profile; (2) the profile of the achievement of the student character survey; (3) Factors causing the misalignment of reading literacy achievement and reading surveys. All three are considered by researchers to have construction as the cause of the problem, although it is still necessary to develop further research. This study recommends the development of test instruments that adapt AKM questions and adaptive-reflective literacy learning models. Schools can realize educational SDgS for their students and become a literacy learning model school based on L1-L3 cognitive levels.